1963
DOI: 10.1128/jb.85.5.1003-1010.1963
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF COPPER ON BACILLUS SUBTILIS

Abstract: Variants have been isolated from liquid cultures of Bacillus subtilis 168 after exposure to copper. The variations manifested are in terms of loss of capacity to be transformed from tryptophan auxotrophy to prototrophy as shown by variant NTCu, and in terms of colony size and altered base composition of the deoxyribonucleic acid as shown by variant SC-22. In addition to the data on altered morphology and chemical composition of the variants, detailed studies on the reversion of one of the variants to B. subtil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1967
1967
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Theoretically, it is conceivable, however, that these organisms might be mutants with altered base compositions. Mutants with altered G + C ratios have been described (Weed, 1963;Gause et al, 1964;DeLey, 1964).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, it is conceivable, however, that these organisms might be mutants with altered base compositions. Mutants with altered G + C ratios have been described (Weed, 1963;Gause et al, 1964;DeLey, 1964).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is important to point out that the availability of the different metals can be influenced by chlorides or other kinds of salts present in natural environments (Babich and Stotzky, 1977). It has often been reported that the toxicity of a pollutant depends on the physicochemical characteristics of the environment into which the pollutant is deposited (Weed, 1963;Babich and Stotzky, 1977;Dean-Ross and Mills, 1989;Flemming and Trevors, 1989). In our work, we have not taken this into account because our aim was to perform a comparative and qualitative study, and not to define the exact physicochemical characteristics that determine the maximum toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The GC content of encapsulated and nonencapsulated staphylococci, of strains recently DNA BASE COMPOSITION OF STAPHYLOCOCCUS isolated from clinical situations, and of the usual stock culture strains of staphylococci were in the range 33.2 to 34.9% ( 13,20). The significant differences reported by Beining and Kennedy (3) when staphylococci are grown in vivo and in vitro were not accompanied by detectable changes in the base composition.…”
Section: Resultsmentioning
confidence: 84%
“…The differential value of GC-content determinations in the Micrococcaceae is in more serious jeopardy if mutants of S. aureus with GC contents of 71% exist, as reported by Gause (8). Substantial change in base composition of an organism has also been reported in Bacillus by Weed (20) and in some very early work on Escherichia by Spirin et al (4).…”
mentioning
confidence: 87%